Financial Stability Overcoming the Crisis and Improving the Efficiency of the Banking Sector - Jones, Randall S.. (OECD Economics Department Working Papers, 2009)
The crisis that originated in mid-2007 in the United States and deepened in September 2008 is the largest peace-time disruption of financial markets since the Great Depression. It was triggered by a number of factors, namely the large amount of lending to subprime borrowers, the expansion of securitisation resulting in a disconnect between loan originators and final investors, the questionable assessments of credit rating agencies and the unprecedented resort to off-balance sheet vehicles. These developments took place during a traditional credit boom and reinforced the skyrocketing of asset prices, erosion of lending standards and under-pricing of risk. The crisis had serious repercussions worldwide, particularly in Europe, given the global nature of financial markets. This paper begins by considering why the Japanese banking system was initially relatively resilient to the deterioration in the global financial system, although there were some secondary effects that are discussed in the following section. The third section outlines the emergency response of the Japanese authorities to the financial crisis, including quantitative measures by the central bank and other institutions and regulatory changes by the Financial Services Agency (FSA). At the same time, the authorities have taken steps to improve the regulatory framework. The fourth section goes beyond the crisis to consider policies to boost chronically low profitability in the banking sector. Measures to promote efficiency in the financial sector by upgrading capital markets and improving the range and quality of financial products are discussed in the following section